Exploring the Potential of Zakah for Supporting Realization of Sustainable Development Goals (SDGs) in Indonesia - Sarah Asmalia; Rahmatina Awaliah Kasri; Abdillah Ahsan (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
Sustainable Development Goals (SDGs) is a universal call to end poverty, protect the planet and ensure that all people enjoy peace and prosperity; goals which are strongly in line with the objective of Islam (maqasid al shariah). Despite of global acceptance of the concept, however, financing issues remain the biggest challenge for realizing the SDGs. Innovative financing through partnership with religious and other institutions, therefore, has been recommended. With this perspective, this study aims to explore the potential of zakah to support financing and realizing the goals in Indonesia. This is done by identifying factors that influence the intention of Muslims to pay zakah and exploring the SDGs’ clusters prioritized to be financed from the zakah funds. The study collected primary data from 304 respondents living in Greater Jakarta area of Indonesia and utilized the Theory of Planned Behaviors (TPB) approach to frame the intentions. It also used descriptive statistics and Structural Equation Modeling (SEM) to analyze the data. The findings suggest that three TPB variables, namely attitudes, subjective norms and behavioral control, have a positive influence on the Muslims’ intention to pay zakat. Additionally, attitudes are influenced by religiosity, knowledge and trust to zakah organizations. Furthermore, of the five objective clusters’ in the SDGs, the people cluster (which includes objectives such as poverty reduction, education and health improvement) received the highest priority in the perceptions of the Muslims regarding the use of zakah for financing SDGs. The findings highlight the potential of zakah in supporting achievement of SDGs in Indonesia, something that might be useful for government, NGOs, zakah organizations and other zakah stakeholders.